DOES INTRAVENOUS TRANEXAMIC ACID REDUCE BLOOD LOSS DURING SURGICALLY ASSISTED RAPID PALATAL EXPANSION? - Emine AKBAŞ; Zerrin ÇEBİ; Erol CANSIZ; Sabri Cemil İŞLER; Sırmahan ÇAKARER (Journal of Istanbul University Faculty of Dentistry, 2017)
Purpose: The purpose of this study was to evaluate the efficacy of tranexamic acid (TXA) in reducing blood loss during surgically assisted rapid palatal expansion (SARPE) procedure. Subjects and Methods: A total of 34 patients (12 male, 22 female) who had been treated surgically under general anesthesia with SARPE including pterygoid disjunction for transverse maxillary deficiency (TMD) were included in this study. The study group (n=17) received intravenous (IV) TXA 10 mg/kg as a preoperative bolus; the control group (n=17) received normal saline solution. Preoperative and postoperative haemoglobin and haematocrit values, intraoperative blood loss, and any blood product transfusion were recorded. Results: Blood loss during SARPE was statistically significantly less in the study group than the control group (p=0.0001). Conclusion: Preoperative IV administration of TXA can effectively control blood loss during when SARPE with pterygoid disjunction is performed.